HUMAN HEALTH EFFECTS OF LEAD IN THE ENVIRONMENT: A MULTI-SOURCE APPROACH OF ELEVATED LEAD EXPOSURES AMONG AT-RISK POPULATIONS IN PITT COUNTY, NORTH CAROLINA, USA - Abioro, Elizabeth May (East Carolina University, 2023)
Despite lead (Pb) in public drinking water has been studied extensively, Pb in homes has received less attention. Elevated Pb level in homes is a growing public health concern as Pb exposure in children is known to cause a multitude of health outcomes, including impaired brain function, behavioral disorders, reduced attention span, memory loss, lower IQ, antisocial behavior, and mood disorders. Most of the homes with higher Pb levels are considered low-income, older, or outdated apartment buildings, where at-risk populations (low-income, minority populations that rely on government assistance to assist with daily needs) typically live and may be unaware of Pb exposure risks. Using secondary data from multiple databases, this ecological study was aimed to: (1) identify potential environmental sources of Pb in different areas of homes in Pitt County, North Carolina, and (2) explore the association between children blood lead level (BLL) and age, gender, race, and sampled years (2018, 2019, 2020) using General Linear Model (GLM). Further, the distribution of minority populations, education level, Pb in homes, and age of homes were mapped using ArcGIS and EPA EJScreen for the United States to determine potential trend. Our GLM results showed a significant positive association between BLL and age of the child (p=0.022); however, there were no significant racial or gender differences in BLL (p>0.05), and that sampled years (2018, 2019, 2020) did not differ significantly in BLL (p>0.05). On average, White children had higher average BLL compared to Black or Other races; while White females, Black males and Other males had higher average BLL compared to their opposite gender. ArcGIS and/or EJScreen mapping showed a general clustering of minority populations and low-income status with the distribution of homes with Pb-based paint in the United States. Within homes, windowsill had more than an order of magnitude higher Pb level (691.8 [mu]g/ft2) compared to other areas (common entry, bedroom, kitchen, and dust) sampled in North Carolina, suggesting windowsill as a prominent source of children Pb exposure in homes. In Pitt County, Greenville had the highest number of homes with elevated Pb compared to other major cities. Overall, children between the age of 1 year 3 month and 3 year 6 month showed a pattern of elevated BLL, while around the 2 yr. age group, the W population had a BLL over the current CDC threshold (3.5 [mu]g/dL) and almost reaching the previous CDC threshold (5 [mu]g /dL), underscoring the need to protect White children that may be disproportionately exposed to Pb in homes. The lack of specific federal and state laws and/or policies around the need to testing all children for BLL calls for an immediate action to implement mandatory testing for children BLL regardless of race or housing conditions. Only then more children could be protected from Pb exposure and health risks.
Keywords: Minority populations; Environmental exposures; Children; Blood lead levels (BLL); Lead policy; Lead; Risk Factors; North Carolina